Helicobacter pylori Chemotaxis Modulates Inflammation and Bacterium-Gastric Epithelium Interactions in Infected Mice - Williams, Susan M. (American Society for Microbiology, 2007)
The ulcer-causing pathogen Helicobacter pylori uses directed motility, or chemotaxis, to both colonize the stomach and promote disease development. Previous work showed that mutants lacking the TlpB chemoreceptor, one of the receptors predicted to drive chemotaxis, led to less inflammation in the gerbil stomach than did the wild type. Here we expanded these findings and examined the effects on inflammation of completely nonchemotactic mutants and mutants lacking each chemoreceptor. Of note, all mutants colonized mice to the same levels as did wild-type H. pylori. Infection by completely nonchemotactic mutants (cheW or cheY) resulted in significantly less inflammation after both 3 and 6 months of infection. Mutants lacking either the TlpA or TlpB H. pylori chemotaxis receptors also had alterations in inflammation severity, while mutants lacking either of the other two chemoreceptors (TlpC and HylB) behaved like the wild type. Fully nonchemotactic and chemoreceptor mutants adhered to cultured gastric epithelial cells and caused cellular release of the chemokine interleukin-8 in vitro similar to the release caused by the wild type. The situation appeared to be different in the stomach. Using silver-stained histological sections, we found that nonchemotactic cheY or cheW mutants were less likely than the wild type to be intimately associated with the cells of the gastric mucosa, although there was not a strict correlation between intimate association and inflammation. Because others have shown that in vivo adherence promotes inflammation, we propose a model in which H. pylori uses chemotaxis to guide it to a productive interaction with the stomach epithelium.